Integrated rearing system proposal for Cantareus aspersus in experimental orchards: Growth models. (June 2022) - Garcia, Anton; Barba, Cecilio; Aragón, Manuel; León, Jose M; De-Pablos-Heredero, Carmen; Gonzalez, Ana
An integrated rearing system for Cantareus aspersus under environmental conditions in an experimental orchard is proposed. In this study, the natural behaviour, circadian rhythms and suitable rearing conditions of the edible snail were optimised to produce homogeneous growth and low variability. The growth was standardised, and growth pattern fit was assessed with various models. One thousand fry were cultured in the orchard, and a random sample of 100 snails were measured weekly for 23 weeks. The rearing system had the following characteristics: snails and earthworms were included in the experimental rearing orchard; a homogeneous group of juvenile snails of the same age and size and high rearing density (500 snails/m 2 ) was used; snails were fed with layers mash ad libitum; and mixed and fringes vegetation was planted in the orchard. A commercial size of 60% of snails was achieved in 21 weeks and 95% in 23 weeks. The different models showed a good fit, and the quadratic model obtained the best fit. This experimental snail orchard proposal can be extended to other areas, although it must be corrected according to different environmental conditions and fit to other species of interest. This experimental model could constitute a viable alternative to traditional models of animal experimentation with mammals, and given its high adaptability, it could be applied in different fields of science.